IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KEBERHASILAN KURIKULUM MERDEKA DI SMP TAHFIDZ AL-QUR’AN WAHDAH ISLAMIYAH ANABANUA - Hasnidar; Mitha Febriani; Hamza; Faridah; Yuli Ardanawati; Besse Herlina; Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a case study research using qualitative descriptive research methods. As a driving school, it is required to implement the Independent Curriculum in accordance with Permendikbud No. 5 of 2022, but there are still several problems or challenges faced in implementing the Independent Curriculum, such as school readiness, infrastructure and especially in terms of human resources. The readiness and competence of the principal is needed in leading and accelerating all school stakeholders in order to achieve success in implementing the curriculum. The purpose of this study is to describe and analyze the implementation of the principal's transformational leadership towards the success of the independent curriculum at SMP Tahfidz Al-Qur'an Wahdah Islamiyah Anabanua. This research was conducted at SMP Tahfidz Al-Qur'an Wahdah Islamiyah Anabanua. There were 15 informants in this study. The data collection techniques used were observation, interviews and documentation using two types of data, namely primary and secondary data. The data analysis used was data reduction, data presentation and drawing conclusions. The results of the study indicate that the principal has successfully implemented transformational leadership by involving all educators and education staff. Transformational leadership provides support for curriculum changes, overcomes obstacles, and creates a conducive environment in achieving the successful implementation of the Merdeka Curriculum at SMP Tahfidz Al-Qur'an Wahdah Islamiyah Anabanua.